DESIGN AND IMPLEMENTATION SEQUENTIAL SEARCH STRATEGY ALGORITHM WITH FREE-SPACE BASED APPROCH TO AVOID OBSTACLES AUTOMATICALLY APPLICATIONS ON SIRUPP - (NIM: 23207139), SUYOTO
Efficient motion planning for robot manipulator arm is required in the use of robots in high level activities. This work addressed for motion planning problem for serial manipulator arm using sequential search strategy algorithm. The approach is done with free-space method. The basic idea behind this approach is to plan the motion of each link successively starting from the base link. Given that the motion of links until link i (including link i) has been planned, that is, the path of one end (the proximal end) of link i + 1 is determined, the motion of link i + 1 is now planned along this collision-free path. Approach to the free-space method is done so that the robot manipulator arm movement more efficient. Tests with several cases concerning the representation of obstacles, backtracking mechanisms, and efficient robot arm movement is done. From the tests result, the trajectory planner able to avoid obstacles with efficient arm movement. The result of trajectory planner implemented in SIRUPP. SIRUPP is a desktop application intended to simulate a robot manipulator movement.